The Validity and Reliability of the Objective Structured Clinical Examination (OSCE) in Pre-internship Nursing Students - Zahra Sabzi; Mahnaz Modanloo; Khadijeh Yazdi; Shohreh Kolagari; Mohammad Aryaie (Golestan University of Medical Sciences, 2018)
Introduction: Validity and reliability are essential criteria for clinical competency assessment tests. This study was conducted to determine the validity and reliability of the Objective Structured Clinical Examination (OSCE) for nursing pre-internship. Methods: This methodological study was done on 36 pre-internship Nursing students of  Golestan  University of Medical Sciences in 2016. Census method was used for sampling. The face validity and content validity of the twelve-station checklist were conducted with the viewpoint and expertise of specialists. The criterion validity was determined by the correlation of the mean scores of theoretical and clinical courses with the total OSCE score, and construct validity was determined by the correlation between score of each stations with total score. The predictive validity was determined by multivariable regression and the reliability was determined through internal consistency. Results: The face validity and content validity of the test checklists were approved by the specialist's panel of the nursing educational departments. The criterion validity was approved by the correlation of the total score of the test with the mean score of the theoretical courses (r = 0.48) and clinical courses (r=0.35). The correlation of the twelve stations with the total score of the test approved the construct validity, and the mean score was the only predictive variable of the test results (P=0.004, r=.68, β=0.49). The internal consistency of the test was (α=0.92). Conclusion: Validity and reliability assessment of clinical competency tests can assure the tools used to determine the readiness of nursing students before entering the field and can resolve learning problems.